Elementos para el diseño de un modelo de internacionalización en la Corporación Universitaria de la Costa CUC ﻿ (2011)
The issue of internationalization is increasingly present in the work of Higher Education Institutions around the world, which is reflected, among other things, the creation and strengthening of the units responsible for international affairs at the IES, involvement and participation in the increasingly active in international academic associations, the growing importance of international cooperation projects in the universities and the manifest need to bring information systems in order on their achievements. We used a descriptive method was used as a literature review regarding the internationalization national and international level Internationalization is the process of integrating an international dimension in research, teaching and service functions in an institution of higher education. (Knight & De With .., 1997) It is important to examine all records of the corporation internationalization in university on the coast, however, because there is no defined policy in this area raises the following research question: What are the factors to be taken into consideration in designing a model of internationalization in CUC? Internationalization is a priority in all HEIs worldwide, through the need for institutional accreditation and to internationalize the college's academic programs have been designed a model of internationalization to strengthen this process in the Corporation University De La Costa CUC which constitute the starting point for the creation of new strategies and the redefinition of existing from the three basic functions of Higher Education, Teaching, Research and Extension in the pursuit of academic excellence